Rheological Characterization of Hydrophylic Gels - Gregolin, Marina Tavares; Chiari, Bruna Galdorfini; Ribeiro, Helena M.; Isaac, Vera Lucia Borges [UNESP] (Taylor & Francis Inc, 2010)
Rheological characteristics of gels were studied, with the focus on their use as a cosmetic base. Some ideal characteristics can be predicted by the rheological characterization, such as the performance, with easy application and without dripping or forming lumps and bubbles. Moreover, it is possible to detect signs of physical instability. The gels were prepared with sodium carboxymethyl cellulose 3% and 5%, with Carbopol 940 (INCI: Carbomer) and with Carbopol Ultrez (INCI: Acrylates/C10-30 alkyl acrylate crosspolymer). The tests performed were yield stress, stress sweep and creep and recovery. The gel with 3% of sodium carboxymethyl cellulose presented the most appropriated behavior and can be indicated as the most suitable cosmetic base.
Keywords: Cosmetic base; hydrophilic gels; rheological characterization; sodium carboxymethyl cellulose; viscoelasticity